2020
DOI: 10.3389/fpls.2020.560682
|View full text |Cite
|
Sign up to set email alerts
|

Kin Recognition in the Parasitic Plant Triphysaria versicolor Is Mediated Through Root Exudates

Abstract: Triphysaria is a facultative parasitic plant in the Orobanchaceae that parasitizes the roots of a wide range of host plants including Arabidopsis , Medicago , rice and maize. The important exception to this broad host range is that Triphysaria rarely parasitize other Triphysaria . We explored self and kin recognition in Triphysaria versicolor and showed that exudates collected from root… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 61 publications
(81 reference statements)
0
3
0
Order By: Relevance
“…DMBQ was first isolated from Sorghum extract (Chang and Lynn 1987) and is considered a major host-derived HIF. However, the amount of DMBQ in Arabidopsis root exudates is too low to account for its HIF activity (Wang et al 2020). In this study, prehaustorium induction by rice and Arabidopsis root exudates was reduced by TFBQ, ASBr and LGR-991 treatments (Fig.…”
Section: Hifs In Host Plant Root Exudatesmentioning
confidence: 59%
See 1 more Smart Citation
“…DMBQ was first isolated from Sorghum extract (Chang and Lynn 1987) and is considered a major host-derived HIF. However, the amount of DMBQ in Arabidopsis root exudates is too low to account for its HIF activity (Wang et al 2020). In this study, prehaustorium induction by rice and Arabidopsis root exudates was reduced by TFBQ, ASBr and LGR-991 treatments (Fig.…”
Section: Hifs In Host Plant Root Exudatesmentioning
confidence: 59%
“…Orobanchaceae parasitic plants can respond to various types of molecules as HIFs, yet the signaling pathways for each HIF and their relationships are largely unexplored. Moreover, although DMBQ was isolated from Sorghum extracts (Chang and Lynn 1986), DMBQ is barely detected in Arabidopsis thaliana root exudates, which have high prehaustorium induction activities (Wang et al 2020). Therefore, the actual molecules in host root exudates responsible for prehaustorium induction are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the types of parasitic plant HIFs in plant root exudates mainly include phenolic acids, quinones, flavonoids, lignin units, cytokinins, and cyclohexene oxides [13], which show different haustorial induction activities for different parasitic plant species. The first HIF discovered, 2,6-dimethoxybenzoquinone (DMBQ), was isolated from sorghum roots and shown to trigger haustorium formation in Triphysaria versicolor and Striga hermonthica [16,17]. Compounds with structures similar to DMBQ, such as phenolic acids (including syringic acid, vanillic acid, and ferulic acid), aldehydes (including syringaldehyde), and flavonoids (including peonidin), have also been reported to induce haustoria in Triphyasria versicolor, Phtheirospermum japonicum, and Striga hermontica [15].…”
Section: Introductionmentioning
confidence: 99%
“…and to receive/emit signals from the environment, and root is the major organ of below-ground performance ( Lal, 1979 ; Callaway and Mahall, 2007 ; Goebel et al, 2011 ; Depuydt, 2014 ). Root exudates are widely accepted as one of the most important mechanisms for below-ground interactions, and some previous research has focused on how root exudates mediate kin recognition ( Biedrzycki et al, 2010 ; Mercer and Eppley, 2014 ; Semchenko et al, 2015 ; Wang et al, 2020 ). Previous studies showed that root exudates mediated kin recognition in Arabidopsis thaliana ( Biedrzycki et al, 2010 ) and Distichlis spicata ( Mercer and Eppley, 2014 ).…”
Section: Introductionmentioning
confidence: 99%